Anti-proliferative activities of the aqueous root extract of Dianthus Thunbergii ss hooper (caryophyllaceae) (2018)
Background: The roots of Dianthus thunbergii SS Hooper are used traditionally in South Africa for the treatment of diabetes, wounds, colic, chest complaints and cancer. This study was aimed at investigating the potential anti-proliferative activities of the D. thunbergii in mammalian cancer cell lines. Materials and Methods: Aqueous and ethanol extracts of D. thunbergii were tested in vitro on two cancer cell lines: human hepato-cellular carcinoma (HepG2) cells and murine insulinoma (INS-1) cells using the 3-(4,5-Dimethylthiazol-2- yl) 2,5-diphenyltetrazolium bromide (MTT) and crystal violet cell viability assays, as well as live-cell fluorescence imaging microscopy. A tentative profiling of the aqueous extract was also carried out using liquid chromatography-mass spectrometry (LC-MS). Results: The aqueous extract (50-200μg/ml) exhibited significant (p<0.05) cytotoxicity in HepG2 cells (IC50<50 μg/ml), while also significantly (p<0.05) decreasing the viability of INS-1 cells (IC50=36.0 μg/ml), although no toxicity was evident in L6 myotubes. Hoechst 33342® and propidium iodide staining of INS-1 cells further revealed significant growth inhibition (p<0.001) of INS-1 cells by the aqueous extract. No meaningful toxicity was, however, obtained with the ethanol extract (IC50 = 204.0 μg/ml). Non-targeted LC-ESI-TOF/MS analysis of the aqueous extract revealed the putative identities of main compounds present in the aqueous root extracts, including some that may contribute to its anti-proliferative action. Conclusion: Taken together, the results showed that the roots of D. thunbergii may represent a potential plant-based sourceof agents with anti-proliferative efficacy.